Escaping the Sisyphean Trap: Systemic Criminal Justice System Reform - Mears, Daniel P. (American journal of criminal justice, 2022)
When calls for reforming criminal justice arise, they frequently target particular—rather than systems-level—problems. This approach can be effective when only a few such problems exist. But it risks worsening rather than improving crime and justice by ignoring many other problems, including system-level issues that undermine efforts to promote safety and justice and to do so cost-efficiently. At the same time, this approach can contribute to continued investment in micro-level changes that ultimately achieve little or fail, in part because they do not address systemic problems. By contrast, systemic change—focused on changes throughout criminal justice and on criminal justice as a system—holds the potential to escape from this Sisyphean vicious cycle and to create greater public safety and justice at less cost.